Analysis of the Paternalistic Leadership Model in Understanding the Behavior of Personnel in Arts Organizations - Riza Bahtiar Sulistyan; Imanita Septian Rusdianti; Emmy Ermawati; Tamriatin Hidayah (Universitas Pendidikan Indonesia, 2026)
This study aims to analyze paternalistic leadership in understanding the behavior of personnel within traditional arts organizations, particularly the Jaranan Sarpo Budoyo group in Jember Regency, East Java. Leadership in arts organizations has distinctive characteristics shaped by cultural values, emotional bonds, and efforts to preserve local traditions. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving the founder, organizational leaders, dancers, gamelan players, the surrounding community, local government, and academics. The findings show that the leadership pattern developed in Sarpo Budoyo is paternalistic, characterized by a leader who acts as a technical director, protector, moral role model, and guardian of cultural values. This leadership model fosters high levels of loyalty, discipline, and commitment among members, thereby ensuring organizational stability and sustainability despite limited resources. However, the leader’s dominance in decision-making also limits opportunities for participation and creative innovation, especially among younger generations. This study demonstrates that paternalistic leadership is a contextual model deeply rooted in local culture, effective in maintaining harmony and the sustainability of traditional arts organizations, but requiring balance through more open dialogue to support creativity and generational renewal.